Resultan Sistem Pemilu dan Sistem Pemerintahan terhadap Pelaksanaan Demokrasi di Indonesia - Anajeng Esri Edhi Mahanani (Fakultas Hukum Universitas Surabaya, 2020)
Problems related to the resultant electoral system and the government system are the focus of the discussion in this study. Types of electoral systems, as well as types of governmental systems are discussed to be able to be a study of the use of electoral systems and government systems. The purpose of discussing this problem is to analyze the electoral system and the government system that are compatible with the implementation of democracy in Indonesia. This research is discussed through normative analysis, and through qualitative methods. The results of the qualitative normative analysis can be seen as follows: First, the results of the analysis show that there is a resultant between the electoral system towards the implementation of democracy in Indonesia as seen from the theory of the people's unity and the representative system. The consultant becomes strong if the general election system used is a purely open proportional electoral system, namely the voter as the supreme sovereignty constitution, can know with certainty who the candidate is and will help determine who is the people's representative. Second, there is a result between the government system and the implementation of democracy, the theory of popular sovereignty and the system of representation. Parliamentary and presidential government systems have their own weak points and strengths. However, the presidential system applied in democratic countries in Indonesia is better, because it tends to be more stable in its accountability. Placing the highest sovereignty as the only party that accepts the responsibility of those who have been elected to the executive and parliamentary institutions. The concept developed is a system of political representation, not as a system of partisan representation . Keywords: Resultan, District System, Proporsional System, Presidensiil, Parlementary